Magnetron discharge intensification for effective deposition of coatings from difficult spray metals - Chunadra, А.G.; Sereda, К.N.; Tarasov, I.K.; Vereshchaka, Y.A. (Вопросы атомной науки и техники, 2020)
The work is devoted to improvement of magnetron discharge parameters based on a standard magnetron sputtering system (MSS) of the MAG-5 type with an additional anode magnetic trap for discharge electrons in the conditions of localization of the discharge zone in the gap between electrodes to prevent charged particles losses. Possibilities of such configuration of MSS for depositing of coatings of materials with low coefficient of sputtering (tungsten) are investigated. The increase of the coating rate has been demonstrated. The mass of the deposited tungsten increased by more than 35% compared to the use of the same MSS without additional anode magnetic trap.